2017
DOI: 10.1108/jfep-01-2017-0001
|View full text |Cite
|
Sign up to set email alerts
|

Recent evidence on political brinkmanship and Treasury yields

Abstract: Purpose This paper aims to analyze how political brinkmanship impacted Treasury yields during the debt ceiling debate in 2015. The results show that the resignation of the House Speaker John A. Boehner caused a significant decrease in Treasury bill yields of one- and three-month maturities. The authors robust analysis indicates that these lower yields have saved US taxpayers several billion dollars in extra tax expenses. This paper provides evidence that lack of political brinkmanship can be very advantageous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Thus, the higher are the interest rates, the higher is the opportunity costs of holding money, and the more T-bills the investors are willing to buy (Nagel, 2014). However, this is not the only one correlation: Nippani and Parnes (2017) found that political brinkmanship and the consequent delays in passing the debt limit reduce the T-bills' price, which leads to increased yields. Thus, the more unstable the political situation in the U.S.A is, the better is for private investors, but worse for the taxpayers.…”
Section: Money Market Instruments As a Tool For Shortterm Private Invmentioning
confidence: 99%
“…Thus, the higher are the interest rates, the higher is the opportunity costs of holding money, and the more T-bills the investors are willing to buy (Nagel, 2014). However, this is not the only one correlation: Nippani and Parnes (2017) found that political brinkmanship and the consequent delays in passing the debt limit reduce the T-bills' price, which leads to increased yields. Thus, the more unstable the political situation in the U.S.A is, the better is for private investors, but worse for the taxpayers.…”
Section: Money Market Instruments As a Tool For Shortterm Private Invmentioning
confidence: 99%
“…On the other hand, the minimum rate (or floor rate) consists of the Central Reserve Bank buying dollars to maintain the exchange rate at that value. This rate varies every day, which will depend on the slope of the exchange rate band (Lukongo & Miller, 2018;Nippani & Parnes, 2017).…”
Section: Introductionmentioning
confidence: 99%